Particle and dispersion liquid thereof, leveling composition and application thereof, semiconductor device and leveling method of substrate for semiconductor device
By using spherical or spherical cerium oxide particles with multiple protruding surface molding, the problem that cerium oxide particles in the prior art is difficult to take into account both high removal rate and low defects in the flattening treatment, and efficient substrate material removal and low defect properties are achieved.
Patent Information
- Application Number
- CN202510130077.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-02-05
AI Technical Summary
It is difficult for existing cerium oxide particles to take into account both the high substrate material removal rate and the low number of surface defects in the flattening process.
It is provided that a spherical or spherical ceria particles with a surface formed with a plurality of raised convex particles, including at least a grain having a particle size greater than or equal to 15 nm.
The material removal rate of cerium oxide particles on the substrate surface is improved, while the surface scratch defects on the substrate surface after treatment are reduced, achieving both high MRR and low defects.
Smart Images

Figure CN119736068A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of planarization treatment, and in particular to a particle and a dispersion thereof, a planarization composition and an application thereof, a semiconductor device and a planarization method for a substrate thereof. Background Art
[0002] Cerium oxide particles are usually used as abrasive particles in the surface planarization of substrates, which helps to increase the material removal rate (MRR) of the substrate to be treated. From the perspective of planarization applications, it is not only hoped that the cerium oxide particles have a higher MRR, but also that they bring fewer surface defects to the substrate during the planarization process. From the perspective of reducing defects, it is hoped that the cerium oxide particles have a morphology close to a standard sphere, but the smooth sphere often reduces its contact with the surface of the substrate to be treated, which is not conducive to the improvement of MRR. Therefore, it is necessary to provide a new type of cerium oxide particles and related applications that can simultaneously have high MRR and low processing defect characteristics. Summary of the invention
[0003] In view of this, the embodiments of the present application provide cerium oxide particles and their dispersion, a planarization composition and their application, a semiconductor device and a planarization method for a substrate therefor, which can achieve both a high substrate material removal rate and low processing defects.
[0004] Specifically, the first aspect of an embodiment of the present application provides a particle, which is a cerium oxide particle, and the cerium oxide particle is a spherical or quasi-spherical particle with a plurality of protrusions formed on the surface, and the spherical or quasi-spherical particle with a plurality of protrusions formed on the surface is composed of a plurality of crystal grains, and the plurality of crystal grains include at least crystal grains with a particle size greater than or equal to 15 nm.
[0005] The cerium oxide particles are spherical or quasi-spherical particles with multiple protrusions on the surface. The presence of multiple protrusions on the surface can improve the MRR of the cerium oxide particles to the substrate surface. The multiple crystal grains constituting the polycrystalline cerium oxide particles at least include crystal grains with a particle size of more than 15nm, which can help to ensure that the MRR of the cerium oxide particles to the substrate is further improved; the spherical or quasi-spherical morphology ensures that when the cerium oxide particles are used as abrasive particles for planarizing the substrate, the number of surface scratch defects caused by the treated substrate is small. Therefore, the cerium oxide particles used in the chemical mechanical planarization process can better balance high MRR and low defectivity.
[0006] In the embodiment of the present application, the sphericity of the cerium oxide particles is in the range of 0.8-1.0. The higher particle sphericity can reflect that the cerium oxide particles provided by the embodiment of the present application are closer to the standard sphere, and the substrate grinding defects caused by them are less.
[0007] In some embodiments of the present application, the plurality of crystal grains at least include crystal grains with a particle size in the range of 15nm-50nm. In this case, the removal rate of the substrate surface material by the cerium oxide particles can be effectively improved, and scratches on the substrate surface after treatment due to the excessive size of the crystal grains can be avoided.
[0008] In the embodiment of the present application, the average width of the protrusions is greater than 10 nm. Protrusions with a wider average width may reflect that the protrusions are obvious extensions existing on the surface of the cerium oxide particles, so as to effectively improve the MRR of the cerium oxide particles to the substrate surface.
[0009] In the embodiment of the present application, the average height of the protrusions is greater than 5 nm. An appropriate average protrusion height can reflect that the protrusions are obvious epitaxies existing on the surface of the cerium oxide particles.
[0010] In the embodiment of the present application, the cerium oxide particles do not have pores. Since the cerium oxide particles are not simple agglomerates of multiple single crystal particles, but polycrystalline particles with good dispersibility, the cerium oxide particles without pores inside or on the surface have good stability during the planarization process.
[0011] In the embodiment of the present application, the trivalent cerium in the cerium oxide particles accounts for more than 30% of the total cerium element. The higher trivalent cerium content in the cerium oxide particles can reflect the higher content of oxygen vacancies on its surface, and its grinding activity is correspondingly higher, thereby further improving its removal rate of the substrate material.
[0012] In the embodiment of the present application, the cerium oxide particles do not contain carbon. The cerium oxide particles provided in the embodiment of the present application are sintered cerium oxide particles, which do not contain organic matter.
[0013] In some embodiments of the present application, the D50 particle size of the cerium oxide particles measured by dynamic light scattering is in the range of 30nm-300nm. The polycrystalline cerium oxide particles have a suitable D50 particle size and are more suitable for surface planarization of substrates used in manufacturing semiconductor devices.
[0014] In some embodiments of the present application, the D50 particle size, D90 particle size, and D10 particle size of the cerium oxide particles measured by dynamic light scattering method satisfy the following: (D90-D10) / D50 is below 0.83. A smaller ratio reflects that the particle size concentration of the cerium oxide particles of the present application is higher and the particle size distribution is narrower.
[0015] In some embodiments of the present application, the specific surface area of the cerium oxide particles is 12-50 m 2 / g.
[0016] In some possible embodiments of the present application, the ratio of the average particle size of the cerium oxide particles measured based on electron microscope photographs to the theoretical average size converted based on the specific surface area of the cerium oxide particles is in the range of 1.5-4.5. The roughness index of the cerium oxide particles of the present application is at an appropriately low level, and the particles are not easy to agglomerate and cause scratches and other defects on the surface of the treated substrate.
[0017] The second aspect of the embodiment of the present application provides a particle dispersion, comprising the particles and a solvent as described in the first aspect of the embodiment of the present application. Since the particle dispersion comprises the cerium oxide particles of the present application, it can achieve a high substrate material removal rate and low defectivity when used in a planarization process.
[0018] In the embodiment of the present application, the solvent includes water, or includes water and a water-soluble organic solvent.
[0019] A third aspect of the embodiments of the present application provides a planarization composition, which includes the particles described in the first aspect of the embodiments of the present application, or includes the particle dispersion described in the second aspect of the embodiments of the present application.
[0020] Since the planarization composition includes the cerium oxide particles of the present application, it is used in a planarization process and can also achieve a higher substrate material removal rate and low defects at the same time.
[0021] In some embodiments of the present application, the pH of the planarization composition is between 3 and 6. The planarization composition has an appropriate pH value, which can ensure that the cerium oxide particles are well dispersed and have a high content therein, so that the planarization composition can achieve a good planarization effect.
[0022] In some embodiments of the present application, the planarization composition further comprises one or more of a pH adjuster, a dispersant, a thickener, a flow improver, and a surfactant.
[0023] In some embodiments of the present application, the content of the cerium oxide particles in the planarization composition is 0.1wt%-1wt%. The appropriate content of the cerium oxide particles in the planarization composition is beneficial to the planarization composition having a higher removal rate of silicon-containing dielectric layers such as silicon oxide.
[0024] The fourth aspect of the embodiments of the present application provides the use of the particle dispersion as described in the second aspect of the embodiments of the present application, or the planarization composition as described in the third aspect of the embodiments of the present application in planarization of a dielectric layer.
[0025] In some embodiments of the present application, the dielectric layer includes one or more of a silicon oxide layer, a silicon carbide layer, or a silicon nitride layer.
[0026] The fifth aspect of the embodiment of the present application provides a method for planarizing a substrate, comprising grinding the surface of the substrate using the planarizing composition as described in the third aspect of the embodiment of the present application. The substrate is ground using the planarizing composition of the embodiment of the present application, and the removal efficiency of unwanted materials on the surface of the substrate is high. After the treatment, the surface of the substrate is relatively flat and has fewer surface defects.
[0027] The present application also provides a method for preparing the cerium oxide particles. The method may include the following steps: (1) mixing an aqueous solution of a base, an aqueous solution of a water-soluble Ce(III) salt, and an acid to obtain a mixed solution; wherein the acid includes an inorganic acid and an organic acid; (2) While maintaining the pH value of the mixed solution at greater than 8.0, heat-treating the mixed solution at a temperature below 100° C., collecting the obtained solid, and drying and calcining the solid at a high temperature to obtain the cerium oxide particles.
[0028] The preparation method can be used to prepare cerium oxide particles that meet the above requirements of the present application, which can be used in a flattening process and have both a high substrate material removal rate and low substrate defectivity. The preparation method is simple in process and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A schematic diagram of the structure of a chemical mechanical planarization device provided in an embodiment of the present application.
[0030] Figure 2 This is a scanning electron microscope (SEM) photograph of the cerium oxide particles prepared in Example 1 of the present application.
[0031] Figure 3 This is a transmission electron microscope (TEM) photograph of the cerium oxide particles prepared in Example 1 of the present application.
[0032] Figure 4 This is the UV-Raman spectrum of the cerium oxide particles prepared in Example 1 of the present application.
[0033] Figure 5 This is the XRD spectrum of the cerium oxide particles prepared in Example 1 of the present application.
[0034] Figure 6 This is a SEM photograph of the cerium oxide particles provided in Example 2 of the present application.
[0035] Figure 7 This is a SEM photograph of the cerium oxide particles provided in Example 3 of the present application.
[0036] Figure 8 This is a SEM photograph of the cerium oxide particles provided in Comparative Example 1.
[0037] Fig. 9 This is a SEM photograph of the cerium oxide particles provided in Comparative Example 2.
[0038] Fig.10 This is a SEM photograph of the cerium oxide particles provided in Comparative Example 3.
[0039] Description of the main figure marks: 100 - chemical mechanical planarization device, 1 - workbench, 2 - planarization pad, 3 - planarization head, 4 - substrate, 5 - planarization liquid supply assembly, 501 - planarization liquid. DETAILED DESCRIPTION
[0040] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0041] Chemical mechanical planarization is a technology that achieves uniform flatness of the substrate surface during the semiconductor device manufacturing process. Its principle is a processing technology that combines chemical corrosion and mechanical removal. Figure 1 A schematic diagram of the structure of a chemical mechanical planarization device provided in an embodiment of the present application. Figure 1 The chemical mechanical planarization device 100 includes a workbench 1, a planarization pad 2 laid on the surface of the workbench 1, a planarization head 3 suspended above the workbench 1, and a planarization liquid supply assembly 5. The workbench 1 and / or the planarization head 3 can rotate under the action of a motor. The substrate 4 to be processed can be fixedly mounted on the planarization head 3. The planarization liquid supply assembly 5 is used to provide a planarization liquid 501. The planarization liquid 501 is generally a chemical solution containing abrasive particles.
[0042] In the chemical mechanical planarization process, the substrate 4 to be processed is fixed at the bottom of the planarization head 3, and its surface to be processed faces the planarization pad 2. The rotating planarization head 3 presses on the planarization pad 2 rotating on the workbench 1 with a certain pressure. The planarization liquid supply component 5 provides the planarization liquid 501 to the planarization pad 2, and the planarization liquid 501 flows between the surface to be processed of the substrate 4 and the planarization pad 2, and is evenly distributed into a layer of liquid film under the transmission and centrifugal action of the planarization pad 2. Through the dual chemical and mechanical effects of the liquid, the surface of the substrate 4 is processed, and a part of the unnecessary material is removed, so that the surface is highly flat.
[0043] For substrates that need to remove a portion of the material such as silicon oxide, silicon nitride, etc., the leveling liquid 501 used is generally a chemical solution containing cerium oxide particles. Cerium oxide particles can form cerium-oxygen-silicon bonds with the surface of materials such as silicon oxide, thereby accelerating the removal rate of silicon oxide materials. Leveling liquids containing cerium oxide particles can also be used to polish silicon nitride, because under aqueous conditions, a portion of the material on the surface of silicon nitride will be converted into silicon oxide and can form cerium-oxygen-silicon bonds with cerium oxide particles, thereby being removed. However, the existing cerium oxide particles used as grinding particles cannot take into account both a higher material removal rate and low grinding defects. In order to obtain a good substrate leveling effect more quickly, the embodiment of the present application provides a cerium oxide particle that can take into account both a higher material removal rate and low grinding defects, and a particle dispersion and leveling composition using the cerium oxide particles, a semiconductor device and a leveling method for a substrate thereof.
[0044] Specifically, an embodiment of the present application provides a particle, which is a cerium oxide particle. The cerium oxide particle is a spherical or quasi-spherical particle with a plurality of protrusions formed on the surface. The spherical or quasi-spherical particle with a plurality of protrusions formed on the surface is composed of a plurality of crystal grains, and the plurality of crystal grains include at least crystal grains with a particle size greater than or equal to 15 nm.
[0045] The cerium oxide particles are spherical or quasi-spherical particles with multiple protrusions on the surface. The presence of multiple protrusions on the surface of the spherical or quasi-spherical particles can improve the material removal rate (MRR) of the cerium oxide particles on the substrate surface, and the grinding ability is relatively high; and the multiple crystal grains constituting the cerium oxide particles include crystal grains with a particle size of more than 15nm, and the crystal grains of this particle size are conducive to further improving the MRR of the cerium oxide particles to the substrate; the spherical or quasi-spherical morphology ensures that when the cerium oxide particles are used as abrasive particles for planarizing the substrate, the number of surface scratch defects caused by the cerium oxide particles to the treated substrate is small. Therefore, the cerium oxide particles are used in the chemical mechanical planarization process, which can simultaneously achieve a high MRR and low defectivity to the substrate.
[0046] In the present application, the spherical or quasi-spherical morphology of the cerium oxide particles can be known from their SEM photos or TEM photos. The cerium oxide particles are not polyhedrons with edges and corners. The cerium oxide particles are composed of multiple grains, that is, the cerium oxide particles are polycrystalline particles. Polycrystalline cerium oxide particles can also be known from their SEM photos or TEM photos. Specifically, each polycrystalline cerium oxide particle is a secondary particle composed of multiple single crystal grains; the polycrystalline particles have grain boundaries ("grain boundaries" are the interfaces between adjacent single crystal grains). Single crystal grains are primary particles and do not have grain boundaries inside. Among them, a protrusion on the surface of the above-mentioned cerium oxide particle can be at least a part of a single crystal grain.
[0047] The size of the average single crystal grains constituting the cerium oxide particles can be calculated based on the half-width of the (111) crystal plane diffraction peak in the X-ray Diffraction (XRD) spectrum of the cerium oxide particles. If the size of the average single crystal grain is greater than 15 nm, then there must be grains with a particle size greater than 15 nm among the multiple crystal grains constituting the cerium oxide particles. Specifically, the diffraction information of the (111) crystal plane diffraction peak can be obtained from the XRD spectrum of the cerium oxide particles, such as the half-width, diffraction angle, etc. Based on this diffraction information, according to the Scherrer formula D = K×λ / (FWHM 111 ×cosθ 111 ) can be used to calculate the particle size of the above single crystal grains. Wherein, λ represents the wavelength of the X-ray used in the XRD test. For copper Kα rays, its wavelength λ is generally 0.154 nm. θ 111 The XRD spectrum of cerium oxide particles represents half of the diffraction angle corresponding to the diffraction peak of the (111) crystal plane. FWHM 111 The half-peak width of the (111) crystal plane diffraction peak of the cerium oxide particle in radians. K is the Scherrer constant, K=0.89. Of course, in other embodiments of the present application, the particle size of the above-mentioned crystal particles constituting the cerium oxide particles can also be obtained by other characterization means (such as high-resolution electron microscopy).
[0048] Optionally, among the plurality of crystal grains, at least 50% or more of the crystal grains have a particle size greater than or equal to 15 nm. Further, the number of crystal grains with a particle size greater than or equal to 15 nm in the plurality of crystal grains constituting a cerium oxide particle accounts for more than 60%, more than 70%, more than 80%, or more than 90%, or even 100%.
[0049] In some embodiments of the present application, the multiple crystal grains (i.e., single crystal grains) constituting the above-mentioned cerium oxide particles include at least crystal grains with a particle size in the range of 15nm-50nm. This is not only conducive to the effective improvement of the removal rate of the cerium oxide particles on the substrate surface material, but also avoids the formation of scratches on the substrate surface after treatment due to the excessive size of the single crystal grains. Similarly, the number of crystal grains with a particle size in the range of 15nm-50nm in the multiple crystal grains constituting a cerium oxide particle accounts for more than 60%, more than 70%, more than 80%, or more than 90%, or even 100%. In some cases, it can be said that the average particle size of the single crystal grains constituting the above-mentioned cerium oxide particles is in the range of 15nm-50nm. Exemplarily, the particle size of the above-mentioned single crystal grains can be specifically 18nm, 20nm, 25nm, 30nm, 35nm, 40nm, or 45nm, etc.
[0050] In the embodiment of the present application, the sphericity of the cerium oxide particles is in the range of 0.8-1.0. The higher particle sphericity can reflect that the spherical or quasi-spherical cerium oxide particles provided in the embodiment of the present application are closer to the standard sphere, and the substrate grinding defects caused by them are less. Among them, the sphericity of the particle is equal to the ratio of the projected area of the particle to the area of a perfect circle with the same circumference as the projected circumference of the particle. The sphericity of the particle SP = 4π × A / L 2 , A and L represent the projected area and projected perimeter of the cerium oxide particles measured from scanning or transmission electron micrographs, respectively. In some embodiments, the sphericity of the cerium oxide particles is between 0.85-1.0, or between 0.9-1.0, etc.
[0051] In the embodiment of the present application, the protrusions are not sharp protrusions. That is, the protrusions are blunt protrusions. Blunt protrusions can help improve the material removal rate (MRR) of the cerium oxide particles on the substrate surface while not causing surface scratches on the treated substrate.
[0052] In an embodiment of the present application, the average width of the protrusion is greater than 10nm. This can reflect that the protrusion is an epitaxial product existing on the surface of the cerium oxide particle, and the existence of the protrusion can be more clearly observed; and the protrusion of this width is not easy to fall off / break from the cerium oxide particle body and remain on the surface of the processed substrate. Among them, the width of the protrusion refers to the maximum value of the distance between any two points on the positive projection contour line of the protrusion on the cerium oxide particle body. In some embodiments of the present application, the average width of the protrusion is greater than 15nm, greater than 20nm, or greater than 30nm, etc. In some embodiments of the present application, the width of each of the protrusions is greater than 10nm, greater than 15nm, greater than 20nm, or greater than 30nm, etc.
[0053] In an embodiment of the present application, on the cerium oxide particles, the average height of the protrusions is greater than 5 nm. An appropriate average protrusion height can reflect that the protrusions are obvious extensions existing on the surface of the cerium oxide particles, so as to effectively improve the MRR of the cerium oxide particles to the substrate surface. Among them, the height of the protrusion refers to the distance between one end of the protrusion away from the body of the cerium oxide particle (i.e., the top) to the bottom of the protrusion. Exemplarily, the average height of the protrusion is above 10 nm, above 15 nm, above 20 nm, or above 30 nm, etc. In some embodiments of the present application, the height of each of the protrusions is greater than 10 nm.
[0054] In some possible embodiments of the present application, in the cerium oxide particles, the spacing between adjacent protrusions is 0-20nm. The spacing between adjacent protrusions is the minimum distance between the contour lines of the orthographic projections of adjacent protrusions on the body of the cerium oxide particle. When the spacing between adjacent protrusions is 0, it means that the two adjacent protrusions are in contact; when the spacing between adjacent protrusions is a non-zero value, it means that there is a gap between the two adjacent protrusions. The spacing between adjacent protrusions is in an appropriate range, which can reflect that the protrusions are arranged more closely, so that the above-mentioned cerium oxide particles with more protrusions on the surface have a larger contact area with the surface of the treated substrate, which is beneficial to the improvement of its MRR.
[0055] In the embodiment of the present application, the cerium oxide particles are dense particles. The cerium oxide particles do not have pores. Since the cerium oxide particles are not simple agglomerates of multiple single crystal particles, but polycrystalline particles with good dispersibility, the interior or surface of the cerium oxide particles do not have pores. This is conducive to improving the structural stability of the cerium oxide particles and the removal efficiency of the substrate surface material.
[0056] In some possible embodiments of the present application, the average number of protrusions in any 50 nm×50 nm rectangular area on the surface of the cerium oxide particles is 3-30. This may reflect that the distribution density of the protrusions on the surface of the cerium oxide particles is relatively high, so that the cerium oxide particles with more protrusions on the surface have a larger contact area with the surface of the treated substrate, which is conducive to increasing the rate at which the cerium oxide particles remove the substrate surface material.
[0057] In an embodiment of the present application, the trivalent cerium in the cerium oxide particles accounts for more than 30% of the total amount of cerium elements. The higher trivalent cerium content in the cerium oxide particles can reflect the higher content of oxygen vacancies on its surface, and its grinding activity is correspondingly higher, so that its removal rate of the substrate material can be further improved. Therefore, the cerium oxide particles are used in the chemical mechanical planarization process, and can simultaneously achieve higher MRR and low defectivity. Exemplarily, the trivalent cerium in the cerium oxide particles can account for more than 32%, more than 35%, more than 40%, more than 45%, more than 50%, more than 55%, more than 60%, or even more than 65%, etc. of the total amount of cerium elements.
[0058] The ratio of trivalent cerium in the cerium oxide particles to the total cerium element can be obtained through the UV-Raman spectrum characterization results of the cerium oxide particles. In the UV-Raman spectrum of the cerium oxide particles, the wave number at 595cm -1 The Raman peaks nearby are attributed to the vibration of intrinsic oxygen defects in CeO2, which can reflect the trivalent cerium content of cerium oxide. The wave number is 465cm -1The Raman peaks nearby can be attributed to the symmetrical vibration of cerium and oxygen atoms in the cubic fluorite structure of CeO2, which can reflect the total content of all cerium elements in cerium oxide. The wave number is 595cm -1 The Raman peak near the wave number 465cm -1 The peak value ratio of the nearby Raman peaks can reflect the proportion of trivalent cerium in the cerium oxide particles to the total amount of cerium elements.
[0059] In some embodiments of the present application, the D50 particle size of the cerium oxide particles measured based on the dynamic light scattering method is within the range of 30nm-300nm. The D50 particle size can be measured using a dynamic light scattering particle size distribution instrument (also referred to as a laser particle size distribution instrument). The D50 particle size represents the particle size value corresponding to when the cumulative volume distribution percentage of the cerium oxide particles reaches 50%. Among them, the polycrystalline cerium oxide particles have a suitable D50 particle size and are more suitable for surface flattening treatment of substrates for manufacturing semiconductor devices. Exemplarily, the D50 particle size can be specifically 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, or 280nm, etc. In some embodiments, the D50 particle size is within the range of 50nm-190nm.
[0060] In some embodiments of the present application, the D50 particle size, D90 particle size, and D10 particle size of the cerium oxide particles measured based on the dynamic light scattering method satisfy: (D90-D10) / D50 is below 0.83. Wherein, the D10 and D90 represent the particle size values corresponding to the cumulative volume distribution percentages of the cerium oxide particles reaching 10% and 90%, respectively. D10, D50, and D90 are measured in the same units (for example, all in nm), and they can all be obtained from the particle size distribution diagram of the cerium oxide particles measured by a dynamic light scattering particle size distribution instrument. "(D90-D10) / D50" can reflect the discreteness of the particle size distribution of the cerium oxide particles. The smaller the ratio, the higher the particle size concentration of the cerium oxide particles and the narrower the particle size distribution. Exemplarily, the (D90-D10) / D50 of the cerium oxide particles is below 0.80, below 0.75, or even below 0.72, etc.
[0061] In some embodiments of the present application, the specific surface area S of the cerium oxide particles can be in the range of 12-50 m 2 / g. The specific surface area S of the cerium oxide particles can be measured by a nitrogen adsorption method (also known as the "BET method"). Since the cerium oxide particles provided in the embodiment of the present application have a plurality of protrusions integrally formed on the surface, their specific surface area is larger than that of a smooth sphere with the same particle size, so that their contact area with the processed substrate is larger, which is conducive to improving the removal rate of the substrate material.
[0062] In some possible embodiments of the present application, the roughness index RI of the cerium oxide particles is in the range of 1.5-4.5. The roughness index RI is the ratio of the average particle size of the cerium oxide particles measured based on an electron microscope photograph (which may be a SEM photograph or a TEM photograph, and the present application will be explained below using the SEM photograph as an example) (recorded as the SEM size or TEM size) to the theoretical average size (recorded as the SSA size) obtained by converting the specific surface area of the cerium oxide particles. For example, RI = SEM size / SSA size. Wherein, SSA size = 6 / (S × ρ); wherein S represents the specific surface area of the cerium oxide particles measured based on the nitrogen adsorption method, and the unit may be m 2 / g; ρ represents the density of cerium (IV) oxide, ρ is equal to 7.22 g / cm 3 Therefore, the SSA size in nm is equal to 0.83 / S×10 3 .
[0063] The roughness index of the spherical or quasi-spherical cerium oxide particles with multiple protrusions on the surface provided by the present application is at a suitably low level, which means that the specific surface area of the particles at the same particle size is at a suitably low level, so that the particles are not easy to agglomerate and cause scratches and other defects on the surface of the treated substrate. For example, the roughness index RI can be 2, 2.5, 3, 3.2, 3.5, 4 or 3.8, etc.
[0064] In the embodiment of the present application, the cerium oxide particles do not contain carbon. That is, the carbon content in the cerium oxide particles is 0. The cerium oxide particles provided in the embodiment of the present application are sintered cerium oxide particles, which do not contain organic matter, so the carbon content in the particles is 0.
[0065] In some possible embodiments of the present application, a cerium source in which cerium accounts for more than 99.9% of the total rare earth elements is used for the synthesis reaction, and the total content of cerium and oxygen in the obtained cerium oxide particles is more than 99.9wt%. Since the cerium oxide particles provided in the embodiments of the present application do not contain carbon elements and other additional metal elements, the total content of cerium and oxygen in the particles is relatively high, and the purity of the cerium oxide particles is relatively high. The cerium element refers to the sum of the contents of trivalent cerium and tetravalent cerium in the cerium oxide particles. In addition, it should be noted that the cerium oxide particles may also have trace impurity elements (such as iron, lanthanum, etc.) derived from the cerium source itself for preparing cerium oxide particles, and the mass ratio of cerium elements to total rare earth elements (including cerium and other impurity rare earth elements) in the cerium source is greater than 99.9%.
[0066] The present application also provides a method for preparing the cerium oxide particles. The method may include the following steps: (1) mixing an aqueous solution of a base, an aqueous solution of a water-soluble Ce(III) salt, and an acid to obtain a mixed solution; wherein the acid includes an inorganic acid and an organic acid; (2) While maintaining the pH value of the mixed solution at greater than 8.0, heat-treating the mixed solution at a temperature below 100° C., collecting the obtained solid, and drying and calcining the solid at a high temperature to obtain the cerium oxide particles.
[0067] In the present application, a mixture of a water-soluble cerium salt, an inorganic acid, an organic acid, and an alkali is subjected to a heat treatment reaction at a temperature below 100°C while maintaining a pH value greater than 8.0, and the solid obtained by the reaction is calcined at a high temperature, so that the obtained cerium oxide particles are spherical or quasi-spherical polycrystalline particles with multiple protrusions integrally formed on the surface, and the particle size of the single crystal grains constituting it is above 15nm, thereby ensuring that the oxide particles can better balance the high substrate material removal rate and low substrate defectivity when used in a chemical mechanical planarization process. In addition, the above-mentioned preparation method can also ensure that the average width, average height, and proportion of trivalent cerium to total cerium elements in the oxide particles are at the higher level mentioned above in the present application. The various characteristics of the oxide particles mentioned above in the present application are all applicable to the cerium oxide particles obtained by the preparation method.
[0068] In step (1), the base includes one or more of ammonia water, alkali metal hydroxide (such as NaOH, KOH), secondary amine, tertiary amine or quaternary amine. In some embodiments, the base is ammonia water. The water-soluble Ce (III) salt may include cerium nitrate, ammonium cerium nitrate or its hydrated salt. In some embodiments, the mixed solution in step (1) may also contain a water-soluble Ce (IV) salt.
[0069] In step (1), the mixing of the solutions can be carried out under an inert atmosphere (such as nitrogen, argon, helium, etc.) or in a sealed container after the air is replaced by an inert gas.
[0070] The inorganic acid may include at least one of nitric acid, sulfuric acid, phosphoric acid, etc. The organic acid may include substituted or unsubstituted C1-C 12 Alkyl carboxylic acid, C2-C 12 Alkenyl carboxylic acid, C2-C 12 At least one of alkynyl carboxylic acid or polycarboxylic acid. 12 Alkyl carboxylic acid refers to the number of carbon atoms in the alkyl group of the carboxylic acid. 12 Alkenyl carboxylic acid refers to the number of carbon atoms in the alkenyl group of the carboxylic acid. 12Alkynyl carboxylic acid refers to the number of carbon atoms of the alkynyl group in the carboxylic acid. The co-existence of an inorganic acid and an organic acid is conducive to ensuring the stability of the pH value of the reaction system and promoting the formation of spherical or quasi-spherical particles. Among them, the acid can be added alone in the form of its own aqueous solution, or first added to an aqueous solution of a soluble Ce (III) salt, and added in the form of a mixed aqueous solution containing an acid and a soluble Ce (III) salt. In some embodiments of the present application, the ratio of the total number of carbon atoms to the number of carboxyl groups in the organic acid is between 2-4. In this way, the presence of the organic acid is more conducive to the formation of spherical or quasi-spherical cerium oxide particles, and after high-temperature calcination, a spherical cerium oxide with obvious surface protrusions is obtained. Exemplarily, the organic acid can be methacrylic acid, acrylic acid, butyric acid, adipic acid, etc.
[0071] In step (2), heat treatment is performed at a temperature below 100°C, mainly to form cerium oxide grains. In a possible embodiment of the present application, the temperature of the heat treatment is 70-95°C, for example, 76°C, 78°C, 80°C, 85°C, or 90°C. Further, in some embodiments of the present application, the temperature of the heat treatment is 76-95°C. Heat treatment of the above-mentioned mixed solution at a higher temperature in the presence of an organic acid is more conducive to ensuring that most of the cerium oxide particles obtained by the reaction are spherical, so that spherical or quasi-spherical cerium oxide particles with large protrusions on the surface can be obtained after subsequent high-temperature calcination.
[0072] In step (2), during the heat treatment, the pH of the mixed solution may change, for example, continuously decrease. However, the present application performs a heat treatment below 100°C on the mixed solution while maintaining the pH value of the mixed solution greater than 8, so that the cerium oxide solid obtained by the heat treatment reaction can obtain cerium oxide particles with obvious protrusions when subsequently subjected to high-temperature calcination, and the high-temperature calcination can trim the morphology of the cerium oxide particles, making the structure more rounded and dense, so that the cerium oxide particles can increase the flattening rate of the substrate without causing obvious surface defects to the substrate. In addition, the high-temperature calcination is also beneficial to ensure that the particle size of the single crystal grains constituting the polycrystalline cerium oxide particles is within a suitably large range (for example, above 15 nm as mentioned above) to improve the MRR.
[0073] The pH value of the mixed solution is maintained at a value greater than 8, which can be achieved by adding alkali during the heat treatment process or by adding an excess of alkali in step (1). It is understood that in step (1), the pH value of the mixed solution is greater than 8.0, for example, greater than or equal to 8.1, greater than or equal to 8.2, greater than or equal to 8.3, or greater than or equal to 8.5.
[0074] In some embodiments of the present application, in step (2), the solid after heat treatment is washed with water and then dried. Optionally, the pH of the solid is adjusted to between 3.5 and 6 after water washing. This can help improve the yield of cerium oxide material. The drying temperature can be 80-120°C. Optionally, the dried solid is pulverized and then calcined at high temperature. This can help improve the effect of high-temperature sintering. Optionally, in some embodiments of the present application, after the high-temperature calcination, the obtained cerium oxide powder can be mechanically dispersed. Exemplary mechanical dispersions may include but are not limited to dry ball milling, wet ball milling, sand milling, microfluidization homogenization, etc.
[0075] In a possible implementation manner of the present application, in step (2), the temperature of the high temperature calcination may be 300-900°C. Exemplarily, the temperature of the high temperature calcination may be specifically 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or 750°C, etc. In some embodiments, the temperature of the high temperature calcination is 500-800°C. In a possible implementation manner of the present application, in step (2), the high temperature calcination may be performed for 1-8 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, etc. Optionally, the high temperature calcination may be performed under an inert atmosphere (such as nitrogen, argon, helium, etc.) to reduce Ce III Oxidation to Ce IV probability.
[0076] In some embodiments of the present application, the high-temperature calcination is carried out in two or more stages. For example, in some embodiments, the first stage is to increase the temperature from room temperature to a first calcination temperature not exceeding 350°C, and keep it warm for 0.5-4h; the second stage is: continue to increase the temperature from the first calcination temperature to a second calcination temperature not exceeding 900°C, and keep it warm for 1-8h. Optionally, the second calcination temperature is greater than 350°C, and can be further above 500°C.
[0077] The present embodiment of the application further provides a particle dispersion, which includes the above-mentioned cerium oxide particles of the embodiment of the application and a solvent.
[0078] In some embodiments of the present application, the solvent is water. In this case, the particle dispersion is specifically an aqueous dispersion of cerium oxide particles. In some other embodiments of the present application, the solvent includes water and a water-soluble organic solvent. Among them, the water-soluble organic solvent should not cause the cerium oxide particles to precipitate or agglomerate. Exemplarily, the water-soluble organic solvent includes but is not limited to one or more of alcohols (such as methanol, ethanol, n-propanol, isopropanol, n-hexanol, etc.), ketones (such as acetone, methyl ethyl ketone, etc.), esters (such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate, etc.), acids (such as acrylic acid, methacrylic acid), etc. Further, in the solvent, the mass of water is greater than the mass of the water-soluble organic solvent. Exemplarily, the mass ratio of water to the water-soluble organic solvent can be between 80 / 20 and 99 / 1.
[0079] In the embodiment of the present application, the pH of the particle dispersion is below 7. This is more conducive to the dispersion of cerium oxide particles and is not easy to settle. In some embodiments, the pH of the particle dispersion is between 4-6.5.
[0080] In some possible embodiments of the present application, the mass proportion of cerium oxide particles in the particle dispersion is in the range of 1%-30%. In some embodiments, the mass proportion is 5%-15%. The particle dispersion has an appropriate solid content, which is conducive to its storage.
[0081] The embodiments of the present application further provide a planarization composition, which includes the cerium oxide particles described above in the embodiments of the present application, or includes the particle dispersion described above in the embodiments of the present application.
[0082] The flattening composition provided by the embodiment of the present application can be used to selectively remove material from the surface of the substrate to achieve flattening / flattening of the substrate surface. Wherein, flattening or flattening the substrate surface is a process of removing material from the substrate surface to form a roughly uniform, flat surface. Flattening can remove unwanted surface morphology and surface defects, such as rough surfaces, agglomerated materials, lattice damage, scratches and contaminated layers or materials. In addition, flattening can also remove excess deposition materials deposited outside the holes when filling the holes in the substrate.
[0083] The planarization composition provided in the embodiments of the present application can be used for chemical mechanical planarization of the surface of a semiconductor substrate or a glass substrate whose surface material is silicon oxide, silicon carbide or silicon nitride. Taking a semiconductor substrate as an example, a dielectric material (such as silicon oxide or silicon nitride) may be deposited thereon. The upper surface of the substrate may become uneven and needs to be planarized / flattened.
[0084] The planarization composition provided in the present application contains the above-mentioned cerium oxide particles, which are spherical or quasi-spherical particles with multiple protrusions on the surface. This allows the planarization composition to remove substrate surface materials at a faster rate when used for planarization of the substrate surface and cause fewer substrate surface defects.
[0085] In some embodiments of the present application, at room temperature, the planarization composition has a removal rate of the silicon oxide film of more than 1900 Å / min. In some embodiments, the removal rate is more than 1940 Å / min, and further more than 2000 Å / min.
[0086] In the embodiment of the present application, the pH of the planarization composition is between 3 and 6, for example, specifically 3, 3.5, 4, 4.5, 5 or 5.5. In some embodiments, the pH of the planarization composition is between 4.5 and 5.5. The planarization composition has an appropriate pH value, which can ensure that the cerium oxide particles are well dispersed and have a high content therein, so that the planarization composition can achieve a good planarization effect.
[0087] It is understood that the planarization composition includes a pH adjuster, and exemplary pH adjusters may include one or more of nitric acid, phosphoric acid, acetic acid, ammonia water, sodium hydroxide, potassium hydroxide, and the like.
[0088] In some embodiments of the present application, the planarization composition further includes one or more additives such as a dispersant, a thickener, a flow improver, a surfactant, etc. These additives can be added as needed. Among them, the dispersant is used to improve the dispersibility of the cerium oxide particles and reduce the probability of sedimentation. Exemplarily, the dispersant may include one or more of polyacrylic acid (PAA), polyacrylamide, etc. The thickener and flow improver are used to adjust the viscosity, fluidity, etc. of the planarization composition.
[0089] In some possible embodiments of the present application, the content of cerium oxide particles in the planarization composition is 0.1wt%-1wt%. In this case, it is more conducive to the removal rate of silicon-containing dielectric layers such as silicon oxide by the planarization composition at a higher level. For example, the content of cerium oxide particles in the planarization composition can be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, etc.
[0090] The embodiments of the present application also provide use of the particle dispersion or planarization composition of the embodiments of the present application in planarization of a dielectric layer.
[0091] The dielectric layer may be a substrate for manufacturing semiconductor devices, or a dielectric layer on the surface of a substrate. In some embodiments of the present application, the dielectric layer may include a silicon dioxide layer, a silicon carbide layer, or a silicon nitride layer.
[0092] The embodiment of the present application also provides a method for planarizing a substrate, comprising grinding the surface of the substrate with the planarizing composition of the embodiment of the present application.
[0093] During the planarization process, the planarization composition can move relative to the substrate to grind the surface of the substrate. Figure 1 In some possible implementations of the present application, the surface of the substrate has a silicon oxide layer, a silicon carbide layer or a silicon nitride layer.
[0094] By using the planarization composition of the embodiment of the present application to grind a substrate, the removal efficiency of unwanted materials on the substrate surface is high, and the surface of the substrate after treatment is smoother and has fewer surface defects.
[0095] The present application also provides a semiconductor device, which includes a planarized substrate obtained by the planarization method of the present application. A functional layer for the semiconductor device can be formed on the planarized substrate, and the bonding force between the functional layer and the planarized substrate is relatively high. That is, the semiconductor device may include a planarized substrate and a functional layer disposed on the planarized substrate. Exemplarily, the semiconductor device may include, but is not limited to, a chip, etc.
[0096] Among them, the planarization, flattening, and chemical mechanical planarization involved in this application all refer to Chemical Mechanical Polishing (CMP) technology.
[0097] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0098] Example 1 2L of dilute ammonia solution with a concentration of 1.5M was prepared using pure water and concentrated ammonia water. 210g of commercially available hexahydrated cerium (III) nitrate was dissolved in a nitric acid aqueous solution with a concentration of 30wt% to obtain 160mL of a cerium salt mixture containing cerium nitrate and nitric acid, wherein the concentration of cerium nitrate was 3M. Under an inert atmosphere, in a 3L reactor, the above-mentioned dilute ammonia water, 5g of methacrylic acid, and a cerium salt mixture were mixed, and then heated to 80°C under stirring conditions, and maintained at 80°C for 4 hours. After cooling to room temperature, the pH of the obtained reaction solution was detected to be 8.3. The solid precipitate in the obtained reaction solution was collected, washed with pure water, dried at 100°C, and then calcined in a semi-enclosed muffle furnace without flowing air (the muffle furnace has an air outlet and the furnace door is not completely sealed), first heated to 300°C, kept warm for 1h, and then continued to heat to 650°C, and kept warm for 5 hours. The light yellow powder obtained after calcination was dispersed in pure water, and the pH was adjusted to 4.5 with nitric acid to obtain a dispersion of cerium oxide particles.
[0099] Preparation of the planarization composition: Add polyacrylic acid (PAA) with a molecular weight of 4000 to the cerium oxide particle dispersion prepared in Example 1, and adjust the pH of the system to 5.0 using ammonia water and nitric acid to obtain a planarization composition with a cerium oxide particle content of 0.25wt%, i.e., a polishing liquid. The mass proportion of PAA in the planarization composition is 0.5wt%.
[0100] The dispersion of the cerium oxide particles of Example 1 was measured using a dynamic light scattering particle size analyzer, and the hydrodynamic average particle size (i.e., D50 particle size) of the cerium oxide particles was measured to be 143 nm. In addition, (D90-D10) / D50 of the cerium oxide particles was measured to be 0.74.
[0101] The cerium oxide particle dispersion prepared in Example 1 was subjected to scanning electron microscopy (SEM) to ensure that the SEM photo of the obtained cerium oxide particles was as follows: Figure 2 As shown. Figure 2 It can be seen that the cerium oxide particles are spherical or quasi-spherical in shape, with many blunt protrusions on the surface. From the SEM photos of more than 100 cerium oxide particles, 100 particles were randomly selected, and the SEM particle size of each particle was measured. The average SEM particle size of the cerium oxide particles was calculated to be 123nm. In addition, the specific area of the cerium oxide particles measured by the nitrogen adsorption method was 18m 2 According to the definition in the previous text of this application, the roughness index of the cerium oxide particles is measured to be 2.66.
[0102] The cerium oxide particle dispersion prepared in Example 1 was subjected to transmission electron microscopy (TEM) analysis, and the SEM image of the obtained cerium oxide particles was as follows: Figure 3 As shown. Figure 3It can be seen that the protrusions on the surface of the cerium oxide particles are integrally formed with the body; the width of the protrusions is generally greater than 10 nm, and the height is greater than 5 nm. The cerium oxide particles are relatively dense.
[0103] In addition, the cerium oxide particle dispersion prepared in Example 1 was subjected to Raman spectroscopy test, the excitation light was ultraviolet light, and an ultraviolet-Raman spectrum was obtained. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the wave number is 595cm -1 The Raman peak near the peak is at wave number 465 cm -1 The peak ratio of the Raman peaks nearby is 0.523, that is, the trivalent cerium in the cerium oxide particles accounts for 33.7% of the total cerium element. In addition, the cerium oxide particles do not contain carbon element as detected by a carbon-sulfur analyzer.
[0104] The cerium oxide particle dispersion prepared in Example 1 was centrifuged and dried to obtain dry cerium oxide particles. The cerium oxide particles were characterized by XRD. The obtained XRD spectrum was as follows: Figure 5 As shown. Figure 5 It can be seen that the half-peak width of the (111) crystal plane diffraction peak is 0.365°, and the 2θ angle of the (111) crystal plane diffraction peak is 28.693°. According to the Scherrer formula, the corresponding single crystal grain size is 22.2nm.
[0105] Flattening test: A polyurethane polishing pad is fixed on the flattening workbench, and a flattening head with a substrate to be processed (specifically a round silicon wafer with a SiO2 film formed on the surface) is installed on the polyurethane polishing pad at a pressure of 3 psi. The rotation speed of the flattening workbench is 60 rpm, the rotation speed of the flattening head is 80 rpm, and the flattening composition provided in Example 1 is supplied to the polishing pad at a flow rate of 100 mL / min. The flattening time of the substrate is 30 s. The flattening rate is obtained by dividing the difference in the thickness of the SiO2 film before and after flattening by the flattening time, and observing whether there are scratches on the surface of the substrate after treatment.
[0106] The planarization test was performed on the planarization composition provided in Example 1, and the removal rate of the SiO2 film on the substrate surface was measured to be 2260Å / min, and no obvious scratches were observed on the substrate surface.
[0107] Example 2 Prepare 500 mL of a 1.8M dilute ammonia solution using pure water and concentrated ammonia water. Dissolve 84 g of commercially available cerium (III) nitrate hexahydrate in a 30% nitric acid aqueous solution to obtain 160 mL of a cerium nitrate solution with a 3M cerium nitrate concentration. In an inert atmosphere, add the above-mentioned dilute ammonia water, 1 g of methacrylic acid and cerium nitrate solution in a 1L reactor, heat to 85°C under stirring, and maintain the reaction at 85°C for 4 hours, and supplement the dilute ammonia solution with a concentration of 1.8M when the pH of the system drops below 8.0 during the reaction. After cooling to room temperature, the pH of the resulting reaction mixture was detected to be 8.2. The solid precipitate in the reaction solution was collected, washed with pure water, dried at 100°C, and then crushed with a high-speed mixer, placed in a muffle furnace, calcined at 250°C for 0.5 hours in an air atmosphere, calcined at 300°C for 1 hour, and then heated to 720°C and calcined for 5 hours in a nitrogen atmosphere. The powder obtained after calcination was dispersed in pure water, and the pH was adjusted to 4.3 with nitric acid to obtain a dispersion of cerium oxide particles.
[0108] The cerium oxide particle dispersion of Example 2 was tested using a dynamic light scattering particle size analyzer, and the D50 particle size of the cerium oxide particles was measured to be 182 nm; (D90-D10) / D50 was 0.64. The morphology of the cerium oxide particles of Example 2 was analyzed using an electron microscope, and the SEM photo thereof is shown in FIG. Figure 6 As shown. Figure 6 It can be seen that the cerium oxide particles are spherical or quasi-spherical in shape, and have many blunt protrusions formed integrally on the surface. From the SEM photos of more than 100 cerium oxide particles, 100 particles were randomly selected, and the SEM particle size of each particle was measured. The average SEM particle size of the cerium oxide particles was calculated to be 176nm. In addition, the specific area of the cerium oxide particles measured by the nitrogen adsorption method was 16m 2 According to the definition in the previous text of this application, the roughness index of the cerium oxide particles is measured to be 3.39.
[0109] In addition, ultraviolet Raman detection showed that the trivalent cerium accounted for 34.5% of the total cerium element in the cerium oxide particles prepared in Example 2. The carbon-sulfur analyzer was used to detect that the cerium oxide particles did not contain carbon. XRD detected that the half-peak width of the (111) crystal plane diffraction peak of the cerium oxide particles prepared in Example 2 was 0.325° and the 2θ angle was 28.673°. The particle size of the corresponding single crystal grains calculated according to the Scherrer formula was 24.95 nm.
[0110] According to the method described in Example 1, the cerium oxide particle dispersion of Example 2 was used to prepare a planarization composition, and the planarization composition was used to perform a planarization test on a circular silicon wafer with a SiO2 film formed on the surface. The removal rate of the SiO2 film was measured to be 2486Å / min, and no obvious scratches were observed on the surface of the silicon wafer.
[0111] Example 3 Use pure water and concentrated ammonia water to prepare 3.2L of dilute ammonia water with a concentration of 0.35M. Dissolve 105g of commercially available hexahydrated cerium (III) nitrate in a nitric acid aqueous solution with a mass concentration of 30% to obtain 160mL of a solution with a cerium nitrate concentration of 3M. Under closed conditions, the above-mentioned dilute ammonia water, 1.5g of methacrylic acid and the above-mentioned cerium nitrate solution are contacted in a 5L reactor, heated to 78°C under stirring conditions, and kept warm at 78°C for 5 hours. After cooling to room temperature, the pH value of the obtained reaction solution was detected to be 8.5. The solid precipitate in the reaction solution was collected, washed with pure water, dried at 100°C, and then heated to 300°C and calcined for 1 hour in a semi-enclosed muffle furnace without air circulation, and then continued to heat to 500°C and calcined for 5 hours. The powder obtained after calcination was dispersed in pure water, and the pH was adjusted to 5.0 with nitric acid to obtain a dispersion of cerium oxide particles.
[0112] The cerium oxide particle dispersion of Example 3 was tested using a dynamic light scattering particle size analyzer, and the D50 particle size of the cerium oxide particles was measured to be 80 nm; (D90-D10) / D50 was 0.76. The morphology of the cerium oxide particles of Example 3 was analyzed using an electron microscope, and the SEM photo thereof is shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the cerium oxide particles are spherical or quasi-spherical in shape, and there are many blunt protrusions on the surface. From the SEM photos of more than 100 cerium oxide particles, 100 particles were randomly selected, and the SEM particle size of each particle was measured. The average SEM particle size of the cerium oxide particles was calculated to be 78nm. In addition, the specific area of the cerium oxide particles measured by the nitrogen adsorption method was 28m 2 According to the definition in the previous text of this application, the roughness index of the cerium oxide particles is measured to be 2.63.
[0113] In addition, the ultraviolet Raman spectroscopy method was used to detect that the trivalent cerium content in the cerium oxide particles prepared in Example 3 accounted for 44.3% of the total cerium element. The carbon-sulfur analyzer was used to detect that the cerium oxide particles prepared in Example 3 did not contain carbon. The cerium oxide particles prepared in Example 2 were subjected to XRD testing. From its XRD spectrum, it was found that the half-peak width of the (111) crystal plane diffraction peak was 0.505° and the 2θ angle was 28.713°. The corresponding single crystal grain size was calculated according to the Scherrer formula to be 16.06nm.
[0114] According to the method described in Example 1, the cerium oxide particle dispersion of Example 3 was used to prepare a planarization composition, and the planarization composition was used to perform a planarization test on a circular silicon wafer with a SiO2 film formed on the surface. The removal rate of the SiO2 film was measured to be 1944Å / min, and no obvious scratches were observed on the surface of the silicon wafer.
[0115] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that high-temperature calcination is not performed. Specifically, after collecting the solid precipitate in the obtained reaction solution, the solid precipitate is washed with pure water until the conductivity of the washing solution is less than 100 μS / cm, and then dispersed in pure water, and the pH is adjusted to 4.5 with nitric acid to obtain a dispersion of cerium oxide particles.
[0116] The cerium oxide particle dispersion of Comparative Example 1 was tested using a dynamic light scattering particle size analyzer, and the D50 particle size of the cerium oxide particles was measured to be 148 nm; (D90-D10) / D50 was 0.78.
[0117] The cerium oxide particle dispersion prepared in Comparative Example 1 was subjected to scanning electron microscopy (SEM) analysis, and the SEM image of the obtained cerium oxide particles is as follows: Figure 8 As shown. Figure 8 It can be seen that the cerium oxide particles are spherical or quasi-spherical in shape, with a rough surface composed of a large number of microcrystals with a width of less than 10 nm, and no obvious protrusions with a width greater than 10 nm. In addition, ultraviolet Raman detection showed that in the cerium oxide particles obtained in Comparative Example 1, trivalent cerium accounted for 65% of the total cerium element. The carbon element in the cerium oxide particles was 0.2% as detected by a carbon-sulfur analyzer. XRD detected that the half-peak width of the (111) crystal plane diffraction peak of the cerium oxide particles obtained in Comparative Example 1 was 0.95°, and the 2θ angle was 28.560°. The particle size of the corresponding single crystal grains calculated according to the Scherrer formula was 8.53 nm, which is not within the range of 15-50 nm mentioned in this application.
[0118] In addition, 100 particles were randomly selected from the SEM photos of more than 100 cerium oxide particles, and the SEM particle size of each particle was measured. The average SEM particle size of the cerium oxide particles was calculated to be 132nm. In addition, the specific area of the cerium oxide particles was measured by nitrogen adsorption method to be 42m 2 According to the definition in the previous text of this application, the roughness index of the cerium oxide particles is measured to be 6.67, which is greater than that of the cerium oxide particles in Example 1.
[0119] According to the method described in Example 1, a planarization composition was prepared using the cerium oxide particle dispersion of Comparative Example 1, and the planarization composition was used to perform a planarization test on a circular silicon wafer having a SiO2 film formed on the surface. The removal rate of the SiO2 film was measured to be 1808Å / min, and there were obvious scratches on the substrate surface.
[0120] Comparative Example 2 The only difference between Comparative Example 2 and Example 2 is that no dilute aqueous ammonia solution was added during the reaction at 85°C.
[0121] The morphology of the cerium oxide particles prepared in Comparative Example 2 was analyzed using a scanning electron microscope. The SEM photo thereof is shown in FIG. Fig. 9 As shown, from Fig. 9 It can be seen that a large number of polyhedral morphologies appear in the cerium oxide particles, the overall sphericity of the cerium oxide particles is poor, and the polyhedrons are mostly particles without obvious protrusions on the surface. In addition, the ultraviolet Raman method was used to detect that in the cerium oxide particles prepared in Comparative Example 2, trivalent cerium accounted for 31.6% of the total cerium element. The carbon-sulfur analyzer was used to detect that the cerium oxide particles did not contain carbon. XRD detected that the half-peak width of the (111) crystal plane diffraction peak in the cerium oxide particles was 0.29°, and the 2θ angle was 28.635°. The particle size of the single crystal grains calculated using the Scherrer formula was 27.96nm.
[0122] According to the method described in Example 1, a planarization composition was prepared using the cerium oxide particle dispersion of Comparative Example 2, and the planarization composition was used to perform a planarization test on a circular silicon wafer having a SiO2 film formed on the surface. The removal rate of the SiO2 film was measured to be 1708Å / min, and there were obvious scratches on the substrate surface.
[0123] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that no organic acid is introduced.
[0124] Use pure water and concentrated ammonia water to prepare 0.4L of dilute ammonia water with a concentration of 1.5M. Dissolve 54g of commercially available hydrated cerium (III) nitrate in a nitric acid aqueous solution with a mass concentration of 30% to obtain 160mL of a solution with a cerium nitrate concentration of 3M. Under an inert atmosphere, add the above-mentioned dilute ammonia water and cerium nitrate solution to a 1L reactor, close the reactor, heat it to 80°C, and maintain the reaction for about 4 hours. After cooling to room temperature, the pH value of the obtained reaction mixture is detected to be 8.4. Collect the solid precipitate in the reaction mixture, wash the solid precipitate with pure water, dry it at 100°C, and then place it in a semi-closed muffle furnace without flowing air for calcination, first calcining at 300°C for 1h, and then calcining at 650°C for 5 hours. Disperse the light yellow powder obtained after calcination in pure water, adjust the pH to 4.5 with nitric acid, and obtain a dispersion of cerium oxide particles.
[0125] The cerium oxide particle dispersion of Comparative Example 3 was tested using a dynamic light scattering particle size analyzer, and the hydrodynamic average particle size (i.e., D50 particle size) of the cerium oxide particles was measured to be 80 nm; (D90-D10) / D50 was 0.76. The morphology of the cerium oxide particles was analyzed using an electron microscope, and the SEM photo thereof is shown in FIG. Fig.10 As shown. Fig.10 It can be seen that the cerium oxide particles are polyhedral in shape and have no obvious protrusions on the surface. In addition, the content of trivalent cerium in the cerium oxide particles was detected by ultraviolet Raman to be 22.0% of the total cerium element. The half-peak width of the (111) crystal plane diffraction peak of the cerium oxide particles prepared in Comparative Example 3 was detected by XRD to be 0.225° and the 2θ angle was 28.547°. The particle size of the corresponding single crystal grains calculated according to the Scherrer formula was 36nm.
[0126] According to the method described in Example 1, a planarization composition was prepared using the cerium oxide particle dispersion of Comparative Example 3, and the planarization composition was used to perform a planarization test on a circular silicon wafer having a SiO2 film formed on its surface. The removal rate of the SiO2 film was measured to be only 1441Å / min, and no obvious scratches were observed on the surface of the silicon wafer.
[0127] The above only expresses the exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.
[0128] It should be understood that the first, second and various numerical numbers involved in this document are only used for the convenience of description and are not used to limit the scope of this application. In this application, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0129] In the description of this application, unless otherwise specified, the meaning of "multiple" refers to greater than or equal to two. "At least one" refers to one or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0130] In addition, the numerical range represented by "-" in this application refers to the range that includes the numerical values recorded before and after "-" as the minimum and maximum values, respectively. In this application, expressions about parameter ranges, such as "greater than or equal to (≥)", "less than or equal to (≤)", "above...", and "below..." all include the number itself. The numerical values and numerical ranges involved in the embodiments of this application are approximate values. Due to the influence of manufacturing processes / testing methods, etc., there may be a certain range of errors, which can be considered negligible by those skilled in the art.
Claims
1. A particle, characterized in that The particles are cerium oxide particles, which are spherical or quasi-spherical particles. The surface of the spherical or quasi-spherical particles is formed with a plurality of protrusions. The spherical or quasi-spherical particles with a plurality of protrusions on the surface are composed of a plurality of crystal grains, and the plurality of crystal grains at least include crystal grains with a particle size greater than or equal to 15 nm.
2. The particle according to claim 1, characterized in that The sphericity of the cerium oxide particles is in the range of 0.8-1.
0.
3. The particle according to claim 1, characterized in that The plurality of crystal grains at least include crystal grains with a grain size ranging from 15 nm to 50 nm.
4. The particle according to claim 1, characterized in that The average width of the protrusions is greater than 10 nm.
5. The particle according to claim 1, characterized in that The average height of the protrusions is greater than 5 nm.
6. The particle according to claim 1, characterized in that The cerium oxide particles have no pores.
7. The particle according to claim 1, characterized in that The cerium oxide particles do not contain carbon element.
8. The particle according to any one of claims 1 to 7, characterized in that The trivalent cerium in the cerium oxide particles accounts for more than 30% of the total cerium element.
9. The particle according to any one of claims 1 to 7, characterized in that The D50 particle size of the cerium oxide particles measured based on a dynamic light scattering method is in the range of 30 nm to 300 nm.
10. The particle according to any one of claims 1 to 7, characterized in that The D50 particle size, D90 particle size, and D10 particle size of the cerium oxide particles measured by a dynamic light scattering method satisfy the following requirement: (D90-D10) / D50 is less than 0.
83.
11. The particle according to any one of claims 1 to 7, characterized in that The specific surface area of the cerium oxide particles is 12-50 m 2 / g.
12. The particle according to any one of claims 1 to 7, characterized in that The ratio of the average particle size of the cerium oxide particles measured based on electron microscope photographs to the theoretical average size converted based on the specific surface area of the cerium oxide particles is in the range of 1.5-4.
5.
13. A particle dispersion, characterized in that: The method comprises the particles according to any one of claims 1 to 12 and a solvent.
14. The particle dispersion according to claim 13, wherein The solvent includes water, or includes water and a water-soluble organic solvent.
15. A planarization composition, characterized in that: The method comprises the particles according to any one of claims 1 to 12, or the particle dispersion according to any one of claims 13 to 14.
16. The planarization composition according to claim 15, characterized in that The pH of the planarizing composition is between 3-6.
17. The planarization composition according to claim 15, characterized in that: The planarization composition further comprises one or more of a pH adjuster, a dispersant, a thickener, a flow improver, and a surfactant.
18. The planarization composition according to any one of claims 15 to 17, characterized in that: In the planarization composition, the content of the cerium oxide particles is 0.1-1 wt %.
19. Use of the particle dispersion according to any one of claims 13 to 14, or the planarization composition according to any one of claims 15 to 18 in planarization of a dielectric layer.
20. The use according to claim 19, characterized in that The dielectric layer includes one or more of a silicon oxide layer, a silicon carbide layer or a silicon nitride layer.
21. A method for planarizing a substrate, characterized in that: The method comprises grinding the surface of the substrate using the planarizing composition according to any one of claims 15 to 18.
22. A semiconductor device, characterized in that: It comprises a planarized substrate obtained by the planarization method as claimed in claim 21.
Citation Information
Patent Citations
Silicon-coating cerium oxide nano-powder material as well as preparation method and application thereof
CN101875873A
Cerium oxide abrasive grains
CN110139907A
Polishing composition containing ceria particles and method of use
US20160257855A1
Cerium oxide production method and a slurry composition comprising the same
WO2010134741A2